CaHY5 Mediates UV-B Induced Anthocyanin Biosynthesis in Purple Pepper - Xiang Zhang; Yunrong Mo; Huidan Zhou; Mengjuan Li; Hong Cheng; Pingping Li; Ruihao Zhang; Yaoyao Huang; Yanyan Wang; Junqiang Xu; Jingjing Liao; Qiaoli Xie; et al. (Agronomy)
Anthocyanins are important flavonoid compounds in plants that are associated with the color formation and antioxidant activity of flowers, fruits, and other organs. Ultraviolet B radiation (UV-B) is one of the key environmental factors that influence anthocyanin accumulation in plants and HY5 is involved in plant photomorphogenesis. However, the molecular mechanism of the signal network of UV-B regulating anthocyanin biosynthesis in capsicum via HY5 remains unclear. In this study, we identified the transcription factor CaHY5, which mediates UV-B signaling, and demonstrated its regulatory role in anthocyanin biosynthesis in purple pepper (Capsicum annuum L.). The results showed that there were photoresponsive and hormone-responsive elements on the CaHY5 promoter that responded to UV-B, indoleacetic acid, salicylic acid, 6-benzyladenine, abscisic acid, and melatonin treatments. UV-B treatment induced the expression of CaHY5 and anthocyanin structural genes. CaHY5 gene-silenced positive plants showed different degrees of the yellowing phenomenon, which affected the expression of the anthocyanin biosynthesis structural gene. The expression levels of anthocyanin biosynthesis-related genes in CaHY5-silenced positive plants increased considerably. This study provides insights into the role of CaHY5 in UV-B-induced anthocyanin biosynthesis in purple pepper.